2008
DOI: 10.1525/as.2008.48.4.673
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Employment in Hong Kong: Trends and Patterns in Comparative Perspective

Abstract: The authors gratefully acknowledge comments by the anonymous reviewers and the support of this study by the Hong Kong Research Grants Council through the project "Flexible Employment and Social Life in Hong Kong: Tracing the Impact of Globalization" (HKUST6054/02H). The able research assistance of Ms. Winnie Chan has been indispensable. Authors' names are arranged alphabetically to indicate equal contribution. Email: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Existing literature on Hong Kong focuses on the characteristics of precarious/nonstandard employment, its trend of expansion, and its social and economic roots. Chiu and his colleagues (Chiu et al 2008) depicted the trend of flexible employment in Hong Kong: while it has always been an important employment type in Hong Kong, its weight further increased after the 1997 Asian Financial Crisis. This was driven by employers' demands for reducing costs, which can be explained by institutional factors such as Hong Kong's colonial tradition, minimal government intervention in labor relations and the underdevelopment of a labor movement.…”
Section: Existing Literature On Precarious Work In Mainland China Andmentioning
confidence: 99%
“…Existing literature on Hong Kong focuses on the characteristics of precarious/nonstandard employment, its trend of expansion, and its social and economic roots. Chiu and his colleagues (Chiu et al 2008) depicted the trend of flexible employment in Hong Kong: while it has always been an important employment type in Hong Kong, its weight further increased after the 1997 Asian Financial Crisis. This was driven by employers' demands for reducing costs, which can be explained by institutional factors such as Hong Kong's colonial tradition, minimal government intervention in labor relations and the underdevelopment of a labor movement.…”
Section: Existing Literature On Precarious Work In Mainland China Andmentioning
confidence: 99%
“…Chiu, So, and Tam (2008) gave details of the way the survey was conducted. With regard to self-arranged training, respondents were asked whether they had, out of their own initiative, taken any work-related training courses in the previous year.…”
Section: Method Data and Measurementsmentioning
confidence: 99%
“…This preference in training is a corollary of the generally high degree of job mobility and short job tenure of Hong Kong employees. Chiu, So, and Tam (2008) noted that the average job tenure of Hong Kong employees had shortened between 1995 and 2004, and was shorter than those in a number of advance western economies. Government surveys on job-changing and labour mobility also show that switching between different employing organisations is common amongst Hong Kong employees (Census and Statistics Department Various years).…”
mentioning
confidence: 99%
“…The provision of part‐time work in Singapore has continued to trend upwards over the past decade, up from 20.1% in 2007 to 36% in 2014, making it the most prevalent FWA (Singapore Ministry of Manpower ). While these figures are encouraging, Chiu, So, and Tam () found that Singapore employees utilise part‐time work options less commonly than their counterparts in western and Asian advanced economies. In 2004, part‐timers accounted for only 4.5% of the Singapore workforce, compared to 25.4% in the UK, 18% in the US, 14.2% in Japan, and 13.3% in Hong Kong (Chiu, So, and Tam ).…”
Section: Introductionmentioning
confidence: 99%
“…While these figures are encouraging, Chiu, So, and Tam () found that Singapore employees utilise part‐time work options less commonly than their counterparts in western and Asian advanced economies. In 2004, part‐timers accounted for only 4.5% of the Singapore workforce, compared to 25.4% in the UK, 18% in the US, 14.2% in Japan, and 13.3% in Hong Kong (Chiu, So, and Tam ). The incidence of part‐time workers in Singapore varies widely across industries (Singapore Ministry of Manpower ), reflecting differing business and organisational needs and supporting findings elsewhere (e.g., Higgins, Duxbury, and Johnson ) that managerial and professional work remains largely the territory of the full‐time working class.…”
Section: Introductionmentioning
confidence: 99%